Controlled substitution of coarse aggregate with waste glass and syringe needle in M20 concrete - Adhikari, Ranjana; Shrestha, Yadin; Amatya, Iswar Man; Motra, Gokarna Bahadur (Journal of Innovations in Engineering Education, 2021)
Certain types of inorganic waste can be reused by substituting the primary materials of M20 concrete in controlled percentage. Inorganic wastes like waste glass and syringe needle are some of its examples which are currently being sent to landfill sites in a large share. This study considers the waste glass (toughen glass, flat glass) generated from the construction site & glass market and autoclaved syringe needle generated as a hospital waste. Waste glass was used to partially replace up to 20% and syringe needle 2% of coarse aggregate in combined form for all concrete mixes. The workability test, compressive strength test and Flexural strength test was conducted to evaluate the effectiveness of the mix. The use of combination of waste glass and syringe needle resulted in decreasing the slump value due to angular grain shape of glass and reinforcing property of needle, whereas the compressive strength noticeably enhanced. With increasing the waste glass and syringe needle percentage the strength gradually increases up to a given limit beyond which it started to decrease. The maximum compressive strength of concrete was obtained at 10% of waste glass and 1% of syringe needle and the value of the compressive strength of the for 28 days of curing is 32.29 N/mm2. The Flexural strength for the sample 2 was observed 3.07 N/mm2.